Tunable NaBH4 Nanostructures Revealing Structure‐Dependent Hydrogen Release. Issue 9 (4th May 2021) - Salman, Muhammad Saad; Rawal, Aditya; Aguey-Zinsou, Kondo-Francois
Abstract : Borohydrides are promising candidates for hydrogen storage and generation assuming these can be tuned to reversibly deliver hydrogen under practical conditions. Nanostructuring of borohydrides has the potential to enable such control but this has remained elusive due to the lack of approaches to effectively prepare and stabilize borohydride nanostructures. Herein, a simple and straightforward method to assemble NaBH4, as a model borohydride, into sphere, cube, and bar‐like shapes using tetrabutylammonium bromide (TBAB), octadecylamine (ODA), and tridecanoic acid (TDA), respectively, is demonstrated. More importantly, the shape of the NaBH4 nanostructures could be tuned from one morphology to another by simply adjusting the ratio of surfactants and this is found to lead to distinct hydrogen properties. In particular, remarkable shifts in the melting points and hydrogen desorption temperatures are observed depending on the NaBH4 morphologies, i.e., spheres, cubes, or bars. For example, for the NaBH4 spheres, hydrogen release starts at ≈50 °C compared to the >500 °C of bulk NaBH4 without any transition metal dopant or catalyst. Observation of such structure‐dependent relationships finally enables new avenues to deliberately tune borohydrides toward nanostructures with specific hydrogen properties otherwise difficult to control. Abstract : The hydrogen properties of sodium borohydride (NaBH4 ) shows for the first time hydrogen properties that are structure‐dependent. This opens new avenues to design controlled nanoarchitectures with predictable hydrogen storage properties.